Lower hydrogen flux leads to larger carbon isotopic fractionation of methane and biomarkers during hydrogenotrophic methanogenesis. (15th February 2020) - Nguyen, T.B.; Topçuoğlu, B.D.; Holden, J.F.; LaRowe, D.E.; Lang, S.Q.
Abstract: The isotopic composition of lipid biomarkers and biomass in sedimentary environments are widely used to infer microbial metabolisms and constrain carbon cycling processes. It has been observed that metabolic energy availability in the form of H2 impacts the stable carbon isotopes of CH4 during hydrogenotrophic methanogenesis, but it is unknown whether this relationship extends to lipids and amino acids. Since lipids and amino acids are long-lived, they can be used to reconstruct past conditions over geologic timescales. Therefore, the controls on their isotopic signatures are important to constrain to better interpret past environments. In this study, the isotopic distributions of carbon metabolized and reduced by the hyperthermophile Methanocaldococcus jannaschii were quantified following growth at 82 °C in a chemostat with high (80–83 µM) and low (15–27 µM) H2 concentrations. As has been shown previously, the stable carbon isotope fractionation factors for CH4 were >15‰ larger in low H2 experiments than in high H2 experiments. Lipid biomarkers and amino acids were similarly impacted with approximately 10‰ larger fractionation factors under low H2 conditions. The increase in fractionation factors can be related to the lower availability of thermodynamic energy, suggesting that even larger fractionation factors would be observed in methanogens living close to their threshold energy needs, as they do in most environments. The resulting isotopic signatures of long-lived lipid biomarkers synthesized by hydrogenotrophic methanogens may become as 'superlight' as those synthesized by archaea carrying out the anaerobic oxidation of methane. These results help to describe the underlying mechanisms that determine the isotopic composition of long-lived biomarkers and provide constraints for interpreting these signatures in the environment.